Efficacy and safety of everolimus with reduced tacrolimus in living‐donor liver transplant recipients: 12‐month results of a randomized multicenter study. Issue 6 (25th January 2018) - Jeng, Long‐Bin; Lee, Sung Gyu; Soin, Arvinder Singh; Lee, Wei‐Chen; Suh, Kyung‐Suk; Joo, Dong Jin; Uemoto, Shinji; Joh, Jaewon; Yoshizumi, Tomoharu; Yang, Horng‐Ren; Song, Gi‐Won; Lopez, Patricia; et al.
Abstract : In a multicenter, open‐label, study, 284 living‐donor liver transplant patients were randomized at 30 ± 5 days posttransplant to start everolimus+reduced tacrolimus (EVR+rTAC) or continue standard tacrolimus (TAC Control). EVR+rTAC was non‐inferior to TAC Control for the primary efficacy endpoint of treated BPAR, graft loss or death at 12 months posttransplant: difference –0.7% (90% CI −5.2%, 3.7%); P < .001 for non‐inferiority. Treated BPAR occurred in 2.2% and 3.6% of patients, respectively. The key secondary endpoint, change in estimated glomerular filtration rate (eGFR) from randomization to month 12, achieved non‐inferiority ( P < .001 for non‐inferiority), but not superiority and was similar between groups overall (mean −8.0 vs. −12.1 mL/min/1.73 m 2, P = .108), and in patients continuing randomized treatment (−8.0 vs. −13.3 mL/min/1.73 m 2, P = .046). In the EVR+rTAC and TAC control groups, study drug was discontinued in 15.5% and 17.6% of patients, adverse events with suspected relation to study drug occurred in 57.0% and 40.4%, and proteinuria ≥1 g/24 h in 9.3% and 0%, respectively. Everolimus did not negatively affect liver regeneration. At 12 months, hepatocellular recurrence was only seen in the standard TAC‐treated patients (5/62; 8.1%). In conclusion, early introduction of EVR+rTAC was non‐inferior to standard tacrolimus in terms of efficacy and renal function at 12 months, with hepatocellular carcinoma recurrence only in TAC Control patients. ClinicalTrials.gov Identifier: NCT01888432. Abstract : This multicenter, open‐label, randomized study in 284 living‐donor liver transplant patients shows that introducing everolimus at day 30 posttransplant with reduced tacrolimus achieves similar efficacy and renal function to a standard tacrolimus regimen, with a comparable incidence of drug‐related adverse events and no hepatocellular carcinoma recurrence in the everolimus cohort at month 12.